Pathogenic Mechanisms of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD)-Associated Hepatocellular Carcinoma - Toru Nakamura; Atsutaka Masuda; Dan Nakano; Keisuke Amano; Tomoya Sano; Masahito Nakano; Takumi Kawaguchi (Cells)
Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third leading cause of cancer deaths worldwide. The etiology of HCC has now dramatically changed from viral hepatitis to metabolic dysfunction-associated steatotic liver disease (MASLD). The main pathogenesis of MASLD-related HCC is the hepatic lipid accumulation of hepatocytes, which causes chronic inflammation and the subsequent progression of hepatic fibrosis. Chronic hepatic inflammation generates oxidative stress and DNA damage in hepatocytes, which contribute to genomic instability, resulting in the development of HCC. Several metabolic and molecular pathways are also linked to chronic inflammation and HCC in MASLD. In particular, the MAPK and PI3K-Akt-mTOR pathways are upregulated in MASLD, promoting the survival and proliferation of HCC cells. In addition, MASLD has been reported to enhance the development of HCC in patients with chronic viral hepatitis infection. Although there is no approved medication for MASLD besides resmetirom in the USA, there are some preventive strategies for the onset and progression of HCC. Sodium-glucose cotransporter-2 (SGLT2) inhibitor, a class of medications, has been reported to exert anti-tumor effects on HCC by regulating metabolic reprogramming. Moreover, CD34-positive cell transplantation improves hepatic fibrosis by promoting intrahepatic angiogenesis and supplying various growth factors. Furthermore, exercise improves MASLD through an increase in energy consumption as well as changes in chemokines and myokines. In this review, we summarize the recent progress made in the pathogenic mechanisms of MASLD-associated HCC. Furthermore, we introduced new therapeutic strategies for preventing the development of HCC based on the pathogenesis of MASLD.